Engine breakdown of lysosomes and related organelles and the resulting physiology - Nina Bakker; Marlieke L. M. Jongsma; Jacques Neefjes (Frontiers in Cell and Developmental Biology)
Late endosomes/lysosomes (LE/Lys) and lysosome related organelles (LROs) move dynamically through cells which involves many levels of regulation. To reach their destination, they need to connect to the motor proteins dynein-dynactin, kinesin or myosin for long-range bidirectional transport along microtubules and short-range movement along actin filaments. This connection depends on various factors at the microtubule, including the MAP- and tubulin-code, as well as adaptors, Rab GTPases and effector proteins marking the LE/Lys and LRO membranes. Mutations affecting this transport results in defective LE/Lys or LRO cargo delivery often resulting in skin, neurological and/or immunological diseases. How LE/Lys and LRO transport is orchestrated and how it fails in disease states, will be discussed.